Static Loading Test and Assessment of Cable-stayed Bridge Which Specialized for Rail Transit - Xiao Yang-Jian; Zhou Lei; Li Xiao-Gang (Archives of Current Research International, 2015)
The Caijia Jialing river bridge which specialized for rail transit is a concrete cable-stayed bridge with main-span 250 m, two pylons and double cable planes. The static loading test includes the following contents: measurement of the initial state of the completed structure, appraisal loading test for the design loading capacity. The assessment analysis based on the tests and theoretical calculations showed that the strength and rigidity indicators for each of the control sections of the bridge satisfy the design requirements.